Presenting a model for effective factors on maintaining and improving the combat power of Iran's armed forces with the environment of physical readiness. - Maysam Dehghan; Habib Honari; Alimohamd Safania; Reza Nikbakhsh (علوم و فنون نظامی, 2023)
Objective: According to the job and mission requirements of the military, they should engage in physical and sports activities. Therefore, this research seeks to answer this question, what is the appropriate model for maintaining and improving the combat power of the Iranian armed forces personnel with a focus on physical fitness?Methodology: This research is mixed in terms of the purpose of application and the method of doing it. The participants in this research were managers and expert commanders in the field of sports in the armed forces. The sampling method was purposeful. The theoretical saturation method was used to estimate the sample size. Data collection tools included interviews and questionnaires. Qualitative analysis and structural equations were used to analyze the data.Findings: The findings showed that the causal factors include: financial, humanitarian, scientific and scientific, educational and research and planning. background conditions including psychological, demographic, structural and behavioral; The main axis includes martial power and championship sports. While the intervening conditions include equipment and facilities and technology; Strategies include structural, economic, social, international, legal, and standardization. These factors will create 12 desirable outcomes.Conclusion: Creating a suitable platform for the development of employees in the field of sports, development of sports infrastructure, development of public sports based on scientific principles and compilation of physical fitness indicators can be among the factors that help maintain and increase the physical fitness of employees in improving the combat power of Iran's armed forces.